Comparing the effect of sequential embryo transfer versus double blastocyst embryo transfer on pregnancy outcomes in intracytoplasmic sperm injection (ICSI) cycles in patients with repeated implantation failure: A randomized controlled trial - Saghar Salehpour; Sedighe Hosseini; Zahra Razghandi; Hossein Hosseinirad; Hasti Ziaee (Taiwanese Journal of Obstetrics & Gynecology, 2023)
Objective: Recurrent implantation failure (RIF) is the main challenge in assisted reproductive technology (ART) practice. Sequential embryo transfer, in which both, cleavage-stage embryo on day 3 and blastocyst on day 5, are sequentially transferred in the same cycle, has been suggested for increasing embryo implantation in RIF patients. The aim of the present study was to compare the effect of sequential embryo transfer versus double blastocyst embryo transfer on pregnancy outcomes in intracytoplasmic sperm injection (ICSI)/frozen embryo transfer (FET) cycles in RIF patients. Materials and methods: This prospective study was enrolled 224 RIF patients undergoing ICSI/FET cycles and randomly divided to sequential and control groups. In sequential group, embryo transfer was conducted on day 3 (cleavage stage) and day 5 (blastocyst stage). In control group, two top-quality blastocysts were transferred on day 5. Results: Two hundred and two couples accomplished the trial, and their data were analyzed. Results demonstrated that sequential embryo transfer on day 3 and day 5 compared to double blastocyst transfer on day 5 significantly increased implantation rate, clinical pregnancy rate and ongoing pregnancy rate in RIF patients (p-value = 0.0142, p-value = 0.0154, p-value = 0.0201, respectively). However, there were no significant differences in terms of chemical pregnancy rate, multiple pregnancy rate, miscarriage rate and ectopic pregnancy rate in the studied groups. Conclusion: Sequential embryo transfer is associated with improved pregnancy outcomes in RIF patients. Further prospective studies with larger sample sizes are required to validate these results.